Do Foreign Direct Investment and Trade lead to Lower Energy Intensity? Evidence from Selected African Countries - Keho, Yaya (International Journal of Energy Economics and Policy, 2016)
The aim of this study is to examine the impact of foreign direct investment (FDI) and trade on energy intensity in a sample of six Sub-Saharan countries. It applies the bounds testing approach to cointegration and Granger causality analysis to annual data covering the time period from 1970 to 2011. The results indicate evidence for energy-reducing effect of FDI in Benin and Nigeria, while in Cote d'Ivoire and Togo, energy efficiency declines as FDI increases. The results also indicate that energy intensity is negatively affected by imports in Cameroon, Cote d'Ivoire and Togo, suggesting that trade improves energy efficiency. Results of Granger causality suggest that in the short-run, energy intensity is caused by FDI in Cote d'Ivoire and Nigeria, and by imports in Cameroon and Nigeria. Keywords: Foreign direct investment; trade; energy intensity. JEL Classifications: C32; F21; Q43